The Gough Map - Its Nature, Conservation History and Display - Clarkson, C; Stiglitz, M (Bodleian Library, 2009)
In 1809 a great treasure of cartography came to the Bodleian Library as part of Richard Gough’s collection. It was given the shelfmark MS. Gough Gen. Top. 16 and is commonly known nowadays as the Gough Map. There have been several studies concerned with the content and signifi cance of the map, but little has been published about its physical properties. Moreover previous works do not focus, to our knowledge, on past phases of restoration, conservation and framing. These issues, together with a systematic study of its storage and display since the map entered the Library, are addressed in this article. To preserve the authenticity of the map it was necessary, before starting any treatment, to consider its physical condition and the possible causes of various past marks and damages. All this posed some new questions that will be analysed, and in part answered, in what follows. New archival discoveries, and related discussion, have been complementary to a lengthy intervention on the map, improving our knowledge considerably and enabling us to carry out more assured conservation treatments.